Experimental study on streamwise interaction of burning compound droplets. (October 2020) - Chen, Chun-Kuei; Yan, Wei-Mon; Lin, Ta-Hui
Abstract: Compound droplet interaction is an important aspect of spray combustion. In this work, the stream wise interaction of burning compound droplets has been conducted experimentally in detail. The constant value of d i = 500 μm is considered for the compound droplet diameter and two values of β = 50% and 85% are used for the H2 O content. The effects of primary distance of compound droplet ( Si ) in the range of 2.5–100 and environmental O2 concentration ( Ω O2 ) in the range of 21%–30% on the flame width, micro-explosion, and evaporation rate are investigated. The experimental results on the compound droplets indicate that, in general the flame length increases as the primary droplet distance decreases. However, as an exception, for a droplet string with the primary distance of 2.5, the trend is reversed due to the collision-merging of the drops. The micro-explosion can be observed due to the nucleation bubble blast in the H2 O core of the compound drop. The flame spread through micro-explosion is observed at S i = 10, and the effects of distance on the droplet evaporation are diminished beyond S i = 30.